The disability movement and the struggle for recognition: Condition for transformative learning of people with disabilities - Chatzipetrou, Anthi (The Greek Review of Social Research, 2025)
The doctoral dissertation presented was prepared by the School of Humanities, Hellenic Open University. According to the committee resolution, the dissertation was approved in June 2023. The committee was consisted of the primary Assistant Professor Zacharias Palios and two committee members, from the University of Crete Professor Giorgos Tsiolis and from University of Athens Professor emeritus Gerasimos Kouzelis. The doctoral dissertation examines the complex relationship between biography, learning and configuration.